PENGARUH WAKTU PENYEMPROTAN DAN KONSENTRASI PACLOBUTRAZOL TERHADAP PERTUMBUHAN BIBIT TREMBESI (Albizia saman Jacq) - Rico Prasetya Candra; Fathurrahman (DINAMIKA PERTANIAN, 2022)
This study aimed to determine the effect of spraying time and concentration of paclobutrazol on the growth of tamarind seeds (Albizia saman Jacq). This research has been carried out Experimentally farm of the Faculty of Agriculture at Universitas Islam Riau, Pekanbaru. The research was carried out from June to September 2020. This study used a Factorial Completely Randomized Design (CRD) by using two factors. The first factor was the spraying time (W), consisting of 3 levels, namely: 25, 50, and 75 days after planting (day) and the second one was the concentration of paclobutrazol (K), consisting of 4 levels, namely: 0, 75, 150, and 225 ppm to obtain 12 treatment combinations with 3 replications, with the total of 36 experimental units. Each unit consisted of 4 plants per plot and 2 were observed as the samples for a total of 144 plants. The Parameters measured were plant height, stem diameter, number of branches, number of leaves, and leaf area. The data were statistically analyzed and presented with the Honest Significant Difference Test (HSD) at the 0.05 level. The results showed that the effect of time and concentration of paclobutrazol was significant on plant height, stem diameter, number of branches, and leaf area. The best treatment was a spraying time of 50 days (W2) and 150 ppm of paclobutrazol concentration (K2). The main effect of real spraying time was on all observed parameters. The best treatment was 50 days after planting (days) (W2). The main effect of paclobutrazol concentration was significant on all observation parameters. The best treatment was a concentration of 150 ppm (K2).